Substance use among school students in Algeria: A sociological approach - Khelfaoui, Fatma (The International tax journal, 2026)
Substance use within the school environment is increasingly recognized as a complex socio-educational issue that poses significant challenges to both educational systems and broader societal stability. Beyond its immediate individual implications, this phenomenon reflects deeper structural and relational dynamics that shape adolescent behavior within contemporary school contexts. From a sociological perspective, drug use among students can be understood as the outcome of multiple interrelated factors, including weakened familial supervision, the growing influence of peer groups, and adolescent tendencies toward experimentation and identity formation. These factors are further reinforced by broader social conditions such as school disengagement, social inequality, and exposure to deviant subcultures. The consequences of substance use are multifaceted and extend beyond academic decline. They include poor scholastic achievement, increased absenteeism, school dropout, and the emergence of deviant behaviors such as aggression and delinquency. Moreover, substance use adversely affects both the physical health and psychological well-being of adolescents, thereby compromising their social integration and future prospects. In contexts such as Algeria, where schools remain central institutions of socialization, addressing this phenomenon requires an integrated preventive strategy grounded in the coordinated efforts of the family, the educational system, and wider social institutions.